2014
DOI: 10.1007/s11033-014-3453-6
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-α and PPARGC1A gene variants have strong effects on aerobic performance of Turkish elite endurance athletes

Abstract: The aim of this study was to investigate the effect of PPAR-α intron 7G>C and PPARGC1A gene Gly482Ser polymorphisms on aerobic performance of elite level endurance athletes. This study was carried out on 170 individuals (60 elite level endurance athletes and 110 sedentary controls). Aerobic performance of athletes and sedentary control groups were defined by maximal oxygen uptake capacity. DNA was isolated from peripheral blood using GeneJet Genomic DNA Purification kit. Genotyping of the PPAR-α intron 7G>C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
2
23
1
2
Order By: Relevance
“…In addition, in four case-control studies, significantly lower frequency of 482Ser allele in Spanish (n ¼ 104), Russian (n ¼ 579), Israeli (n ¼ 74), and Polish (n ¼ 92) elite endurance-oriented athletes has been reported [30,133,148,149]. However, while Maruszak et al [116] and He et al [150] have not replicated the same results in 213 Polish and 235 Chinese endurance athletes, respectively, Tural et al [136] have shown an opposite association; that is, 60 Turkish endurance athletes had significantly lower frequency of the Gly482 allele than 110 controls. Additionally, He et al [150] in the study of Chinese athletes have revealed the prevalence of the A allele of the functionally relevant rs4697425 A/G polymorphism in 127 female endurance athletes in comparison with controls (but not in 194 male endurance athletes).…”
Section: Ppargc1a Gly482 and Rs4697425 A Allelesmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, in four case-control studies, significantly lower frequency of 482Ser allele in Spanish (n ¼ 104), Russian (n ¼ 579), Israeli (n ¼ 74), and Polish (n ¼ 92) elite endurance-oriented athletes has been reported [30,133,148,149]. However, while Maruszak et al [116] and He et al [150] have not replicated the same results in 213 Polish and 235 Chinese endurance athletes, respectively, Tural et al [136] have shown an opposite association; that is, 60 Turkish endurance athletes had significantly lower frequency of the Gly482 allele than 110 controls. Additionally, He et al [150] in the study of Chinese athletes have revealed the prevalence of the A allele of the functionally relevant rs4697425 A/G polymorphism in 127 female endurance athletes in comparison with controls (but not in 194 male endurance athletes).…”
Section: Ppargc1a Gly482 and Rs4697425 A Allelesmentioning
confidence: 92%
“…Individuals homozygous for the C allele had a threefold greater and heterozygotes had a twofold greater increase in LV mass than G allele homozygotes. It was demonstrated that the frequency of the PPARA rs4253778 GG genotype and G allele was higher in 491 Russian endurance-oriented athletes (P ¼ 0.0001) [132], 74 elite Israeli endurance athletes (P ¼ 0.051) [133], 55 elite Polish rowers (P ¼ 0.009) [134], Polish combat athletes (P ¼ 0.01) [135], and 60 Turkish endurance athletes (P < 0.001) [136] compared to controls and/or sprinters. In accordance with the hypothesis, mean percentage of type I muscle fiber was higher in GG homozygotes than in CC genotype subjects (in a study of 40 physically active healthy men) [132].…”
Section: Ppara Rs4253778 G Allelementioning
confidence: 99%
“…As a whole, this is speculated to increase oxidative capacity, increase resistance to fatigue and enhance endurance performance. Several studies in humans have linked PPARGC1A genotypes (Gly182Ser) to endurance or sprint aptitude . Of particular significance, a lower frequency of the PPARGC1A Ser482 allele and a higher frequency of the PPARA GG genotype were found in endurance athletes.…”
Section: Equine Performance Genes As Possible Candidates For Equine Gmentioning
confidence: 99%
“…Ayrıca, ADE, anjiyotensinojen [angiotensinogen (AGT)] ve monositrik genleri ile insüline benzer büyüme faktörü-1, peroksizom proliferatör aktif reseptör, C-aktinin, beta adrenerjik reseptörünü kodlayan ve nükleer solunum faktörü olan genlerinin de atletik performansı etkilediği saptanmıştır. 4,20,24 Günümüzde kalıtımının, atletik performansa etkisinin %66 olduğu tahmin edilmektedir. Fakat, bazı spor branşlarında kritik öneme sahip olan boy uzunluğunda bu değerin %80 olduğu rapor edilmiştir.…”
Section: Atleti̇k Performans Ve Bi̇leşenleri̇unclassified